Emotional maturation and its relation with leading behavior among the lecturers of Baghdad university (Journal Of Educational and Psychological Researches, 2017)
Self is the main factor of personality and the acceptance of others where each of them are connecting and plays an important role in emotional maturation. The researches affirmed that the leading behavior depending on good human relations between the employers and the employees will enhance their goals and the goals of the institution at the same time . This study aims to measure the emotional maturation among the leactures of the university according to sex variable and identify the correlation between emotional maturation and the level of leading behavior among the lecturers of the university. The sample consists of two samples where the lst is to build the measwe consisting of (200)males and famales lecturers and the 2nd which is the main application one consisting of (400) males and females lecturers where there are (200) males and (200) females. And the sample selected randomly. The researcher res to humber of results : 1. The sample, according to the comparison between the mean and hypothetical one , characterized with emotional maturation at (0,05) significance level. 2. The sample ,according to the comparison between the meam and hypothetional one, characterized with leading at (0,05) sighifigance level . 3. There are no statistical significant differences in the scale of leading behavior according to sex variable at (0,05) signifigance level. 4. There are no statistical significant differences in the seals of emotional maturation according to sex variable at (0,05) significance level. 5. There is high positive correlation between the scale of emotional maturation and the scale of leading behavior which is (0,21) among the lecturers of the university at (0,05) significance level. The researcher reaches to number of suggestions and conclusions